KONVERSI NILAI KUANTITATIF MENJADI KUALITATIF DALAM EVALUASI PENDIDIKAN DAN KINERJA GURU PAI MENGGUNAKAN PENILAIAN ACUAN NORMA - Muhammad Fathin Abdul Ghoffar; Nur Aziz; Ahmad Rasyid (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Educational evaluation is a crucial instrument for ensuring the quality of learning processes and outcomes. In Islamic Religious Education (PAI), evaluation focuses not only on cognitive mastery but also on the development of students' attitudes, character, and spirituality. A frequently encountered problem is the dominant use of quantitative scores, which fail to comprehensively reflect the quality of learning outcomes or the performance of Islamic Religious Education (PAI) teachers. Therefore, efforts are needed to convert quantitative scores into qualitative scores to make evaluation results more meaningful, communicative, and contextual. This article aims to examine in-depth the concept of converting quantitative scores into qualitative scores in the evaluation of Islamic Religious Education (PAI) teacher performance and education using Norm-Referenced Assessment (NAA). This research employed a qualitative approach, utilizing literature review methods from relevant books, scientific journals, and academic sources. The results indicate that NAA is effective for mapping the relative position of students and PAI teachers within their groups, but has limitations in depicting the achievement of ideal competencies and moral-spiritual aspects. Therefore, integrating NAA with norm-referenced assessment and a qualitative approach is essential for holistic evaluation of Islamic education.